The neurological complications after covid-19 in children - Ziółkiewicz, Aleksandra; Więsyk, Piotr; Jartych, Aleksandra; Żybowska, Monika; Cichocka, Agnieszka; Rzewuska, Anna; Chrościńska-Krawczyk, Magdalena (Journal of Education, Health and Sport, 2022)
Studies have shown that during the pandemic period, children under 5 years of age accounted for 1.8% of COVID-19 cases. After covid complications are now a major concern and represent a new disease entity known as PIMS and MIS-C. Many studies have been conducted on the pathomechanism of the virus and the clinical manifestations it causes in adults, including neurological complications. Symptoms are mainly associated with central and peripheral neurological disorders, ranging from mild (headache, fever, cough, pharyngitis, rhinitis and anosmia) to severe (stroke or Guillain-Barré syndrome). Dyspnoea or respiratory failure is seen in approximately 11.7% of young patients. Although SARS-CoV-2 mainly occupies the respiratory system, about 10% report gastrointestinal symptoms. CT abnormalities of the chest of children are less frequent and milder than in adults, and include opacities of frosted glass and patchy shadows. In many cases, elevated CK-MB levels have also been noted, indicating possible myocardial damage. Children and adolescents contribute to an increasing proportion of all Covid-19 cases. It can be due to the emergence of highly infectious variants of the virus. Many drugs have been tried in children both antiviral, antimalarial, corticosteroids and intravenous immunoglobulin or selective cytokine brokers. The only effective method of prophylaxis is two doses of BNT162b2 vaccine given 21 days apart.